Birth prevalence of congenital heart disease: A cross-sectional observational study from North India - Anita Saxena; Anurag Mehta; Mamta Sharma; Sudha Salhan; Mani Kalaivani; Sivasubramanian Ramakrishnan; Rajnish Juneja (Wolters Kluwer Medknow Publications, 2016)
Objective: To assess the birth prevalence and pattern of congenital heart disease (CHD) using echocardiography in babies born in a community hospital of North India. Methods: A cross-sectional observational study conducted over a period of 3 years. Newborns born over a specific 8-h period of the day were recruited in the study. They underwent routine clinical examination and pulse oximetry, followed by screening echocardiography for diagnosing a CHD. Results: A total of 20,307 newborns were screened, among which 874 had abnormal echocardiograms; 687 had insignificant CHDs, 164 had significant CHDs, and 24 had other abnormal cardiac findings. The birth prevalence of significant CHDs was 8.07 per 1000 live births; 131 newborns had an acyanotic CHD (79.9%) and 33 a cyanotic CHD (20.1%). Ventricular septal defect (VSD) was the most common acyanotic CHD, present in 116 newborns, giving a prevalence of 5.7/1000 live births. Among the cyanotic CHD, transposition of great arteries was most common (prevalence 0.34/1000 live births). Conclusion: The CHD birth prevalence in our study is similar to the reported worldwide birth prevalence. Acyanotic CHD (mostly VSD) is seen in about three-fourths of babies born with CHD. The more sinister cyanotic CHD is present in remaining 25%.